Resource management in sliced networks with mobile edge computing for B5G and 6G - Qian SUN; Lin TIAN; Yiqing ZHOU; Chen FENG; Yuanyuan WANG; Jihua ZHOU (Dianxin kexue)
With the time-delay sensitive compute-intensive tasks growing exponentially, 5G and future 6G mobile cellular communication networks will form differentiated network slices with edge computing resource to service the multiple communication services.To achieve this, the wireless frequency and edge computing resources will be shared among the network slices, thus the efficient management of the resources is of great importance.The demands of resources management in the life duration of the network slice was analyzed.Then the research progress of the corresponding technologies for slices, i.e., access control, resources allocation and stimulating cooperation among terminals, were summarized.And the open research issue was given.Thus, the resources are managed efficiently for the slices with edge computing resource.